Teaching during the pandemic: an exploratory study in Portuguese and Brazilian secondary education teachers: exploratory study in Portugal and Brazil reflecting the need for teacher training - Trindade, Sara Dias (2022)
The present study takes as a starting point the COVID-19 lockdown to which Portuguese and Brazilian schools were confined during 2020, to trace the scenario regarding the training needs of secondary education teachers in terms of digital skills. The research questions seek, firstly, to understand how the transition from face-to-face environments to digital environments was carried out in those countries and, secondly, to assess how to improve digital skills in education when considering a post-pandemic future. The results, obtained from responses by 300 teachers to a questionnaire survey, are in line with the conclusions of the intense research that has been conducted in this area: the COVID-19 pandemic has made teachers’ digital training more urgent, and has highlighted the importance of integrating digital environments in education, both as a strategy for the continuity and sustainability of education itself, and as a fluid space that allows the development of practices that enhance quality learning. The analysis also allows us to perceive the differences and similarities in terms of education between two countries that share the same language and have historical proximity, but different socioeconomic indices.